2011
DOI: 10.3390/molecules16042960
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Spectral Properties of Substituted Tetraphenylporphyrin Iron Chloride Complexes

Abstract: A series of substituted tetraphenylporphyrin iron chloride complexes [RTPPFe(III)Cl, R=o/p-NO2, o/p-Cl, H, o/p-CH3, o/p-OCH3] were synthesized by a novel universal mixed-solvent method and the spectral properties of free base porphyrins and iron porphyrin compounds were compared with each other. The experimental results showed that the one-pot mixed solvent method was superior to the two-step method in the yields, reaction time and workup of reaction mixtures for the synthesis of iron porphyrin compounds. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 32 publications
4
67
0
1
Order By: Relevance
“…38 In the IR spectra shown in Fig. 1(e), it is observed that aer Fe 3+ sensing, a new peak has been appeared $1000 cm À1 which is due to the Fe-N bond stretching vibration 39 whereas the small decrease in the intensity of the -NH stretching vibration indicates to the successful formation of Fe-N bond. Aer Fe 3+ attachment, shiing in the n-p* transition of the NCQD sample also implies to the interaction of Fe 3+ and NCQD as shown in the UV spectra [ Fig.…”
Section: Characterization Of Novel Ncqds-fe 3+ Complexmentioning
confidence: 95%
“…38 In the IR spectra shown in Fig. 1(e), it is observed that aer Fe 3+ sensing, a new peak has been appeared $1000 cm À1 which is due to the Fe-N bond stretching vibration 39 whereas the small decrease in the intensity of the -NH stretching vibration indicates to the successful formation of Fe-N bond. Aer Fe 3+ attachment, shiing in the n-p* transition of the NCQD sample also implies to the interaction of Fe 3+ and NCQD as shown in the UV spectra [ Fig.…”
Section: Characterization Of Novel Ncqds-fe 3+ Complexmentioning
confidence: 95%
“…The N-H bond stretching and bending frequencies of TCPP located at 3200 cm -1 and 970 cm -1 disappeared when iron ion was inserted into the porphyrin ring, and a characteristic Fe-N band appears at 1000 cm -1 , which indicates the formation of an iron porphyrin compound [39]. The bands at about 3415 cm -1 , 1740 cm -1 and 1200 cm -1 were assigned to the O-H, C=O and C-O bonds of the carboxylic groups, respectively.…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…It is found that the ν(N-H) stretching frequency of free base porphyrins are located at ~3400-3320 cm -1 (Sun et al, 2011) and disappeared when thallium metal ion was inserted into the porphyrin ring. There is an additional Tl-N stretch vibration at 400-500 cm -1 in metalated complexes indicating the formation of Tl(III) porphyrins.…”
Section: Infrared Spectroscopymentioning
confidence: 99%